Parfit on Act Consequentialism. Issue 4 (December 2020) - de Lazari-Radek, Katarzyna; Singer, Peter
Abstract: In the first two volumes of On What Matters, Derek Parfit argues that three major normative theories – Kantianism, Contractualism and Rule Consequentialism – are, in their most defensible forms, compatible, and can be reconciled in what he calls 'Triple Theory'. This has led many to assume that Parfit does not believe that Act Consequentialism is a defensible form of Consequentialism. We draw on correspondence with Parfit to show that this assumption is incorrect. We then consider Parfit's efforts, in the third volume of On What Matters, to narrow the differences between Act Consequentialism and the triple theory, in part by treating impartial rationality as an external rival to morality, in much the same way that egoism is an external rival to morality. We argue that Parfit's attempts to bridge the gap between Act Consequentialism and Triple Theory meet with only limited success.